1995
DOI: 10.1042/bj3060557
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,2,3-trisphosphate and inositol 1,2- and/or 2,3-bisphosphate are normal constituents of mammalian cells

Abstract: 1. An inositol trisphosphate (InsP3) distinct from Ins(1,4,5)P3 and Ins(1,3,4)P3, which we previously observed in myeloid and lymphoid cells [French, Bunce, Stephens, Lord, McConnell, Brown, Creba and Michell (1991) Proc R. Soc. London B 245, 193-201; Bunce, French, Allen, Mountford, Moore, Greaves, Michell and Brown (1993) Biochem. J. 289, 667-673], is present in WRK1 rat mammary tumour cells and pancreatic endocrine beta-cells. 2. It has been identified as Ins(1,2,3)P3 by a combination of oxidation to ribito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…We should clarify that the importance of InsP 6 stems both from its own role and as a platform from which other regulatory molecules are derived. Examples of the latter include the inositol pyrophosphates (Barker et al, 2009b;Shears et al, 2011;Saiardi, 2012) (see section IV) or the Ins(1,2,3)P 3 -based inositol polyphosphates with iron-binding properties (Barker et al, 1995;Spiers et al, 1996;Irvine, 2005). In terms of the direct effects of the molecule, two or three different modes of operation for InsP 6 can be identified.…”
Section: Novel Roles Of Insp 6 Outside the B-cellmentioning
confidence: 99%
See 1 more Smart Citation
“…We should clarify that the importance of InsP 6 stems both from its own role and as a platform from which other regulatory molecules are derived. Examples of the latter include the inositol pyrophosphates (Barker et al, 2009b;Shears et al, 2011;Saiardi, 2012) (see section IV) or the Ins(1,2,3)P 3 -based inositol polyphosphates with iron-binding properties (Barker et al, 1995;Spiers et al, 1996;Irvine, 2005). In terms of the direct effects of the molecule, two or three different modes of operation for InsP 6 can be identified.…”
Section: Novel Roles Of Insp 6 Outside the B-cellmentioning
confidence: 99%
“…However, it still may fulfill this role in other cellular contexts in vesicles or other subcellular organelles and more widely in nutrition, in which its abundance and chelating properties are known to cause malnutrition in developing countries (Zhou and Erdman, 1995). Furthermore, the InsP 6 breakdown product Ins(1,2,3)P 3 (Barker et al, 1995) has now been subject to the same rigorous assessment as InsP 6 (Veiga et al, 2009) but, in contrast, remains one of the best candidates in the mammalian cell for both complexing iron and preventing iron-catalyzed free radical cascades, acting therefore as a potent antioxidant. The importance of InsP 6 as an antioxidant then becomes as the reservoir from which Ins(1,2,3)P 3 is derived.…”
Section: Novel Roles Of Insp 6 Outside the B-cellmentioning
confidence: 99%
“…None of the isomers detected is unique to plants though d/l-Ins(2,4,5) P 3 and Ins(1,2,3) P 3 have only occasionally been reported in vivo in any kingdom Hanke, 1992, 1996b;Barker et al, 1995). Although Ins(1,4,5) P 3 is one of only a few InsP 3 s identified to date, it appears that this isomer is only a minor component of the inositol phosphate complement of higher plants.…”
Section: Inositol Trisphosphates In Plantsmentioning
confidence: 99%
“…It occurs in non-highly differentiated cells (mesophyll cells) in the fronds and turions of S. polyrhiza, in root cortex cells of Arabidopsis, and in terminally differentiated cells in barley aleurone. It is likely that the route of Ins(1,2,3) P 3 generation is shared in monocots and dicots and perhaps also in animal cells (Barker et al, 1995), where it has been shown that Ins(1,2,3) P 3 is a product of InsP 6 breakdown by cell homogenates. Clearly, Ins(1,2,3) P 3 is not restricted to specialized cells or storage tissues in plants, so we should consider a general "housekeeping" function for this isomer.…”
Section: Metabolic Origins Of Inositol Trisphosphates In Plants: Inspmentioning
confidence: 99%
See 1 more Smart Citation